Pengaruh Kebijakan Mutasi Pegawai Negeri Sipil Terhadap Peningkatan Kinerja Pegawai di Dinas Pendidikan Pemuda dan Olahraga Kabupaten Kepulauan Talaud - Mahda, Liany Tiara; Lengkong, florence Daicy; Laloma, Alden (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : Introduction One of the purposes of the implementation of mutations policy is to seek the rightperson in the right place "the right man on the right place". Will thus be able to improve employeeperformance. Although we have already arranged for the purpose of putting the right people in the rightplace, but it does not mean the problem has been completed. A work that is routine may lead to boredom,so that in these circumstances the possibility of his enthusiasm and excitement down. This can happendespite the fact that the placement in place the right people have been executed. For that reason inmutates we must see to it that a new task is still in line with the duties and previous work. Therefore, thisstudy aimed to determine the effect of policy transfer of civil servants to the improvement of theenvironmental performance of employees in the education department of youth and sports district Talaudislands. Methods The method used is quantitatively using simple linear regesi analysis, and correlationanalysis is simple. And the sample studied were 30 people, in the data collection techniques using SampleRandom Sampling technique, a questionnaire (questionnaire) or a list of questions, and observations.Results The results of the overall analysis shows that the policy of transfer of civil servants have a positiveinfluence on the improvement of the performance of employees in the Ministry of Youth and SportsTalaud Islands. Conclusion As the results of this research as well as theoretical idea then it can be statedthat the policy of transfer of civil servants have a positive influence on employee performanceimprovement.Keywords: Policy, Mutations, Increased Perform